TYPOLOGY OPTIONS OF GLOBALISMS IN THE RUSSIAN LANGUAGE - Karimxodjayev, Niyetbay Sharipovich; Isakov , Esen Islambekovich (Educational Research in Universal Sciences, 2023)
“The functioning of globalisms in modern Russian” is devoted to identifying the derivational potential of globalisms, the features of their functioning in modern Russian, and also presents options for the typology of globalisms. An analysis of the functioning of globalisms in the Russian language makes it possible to identify a certain pattern: each newly emerging slang unit not only provides informal communication for the speakers of this jargon, but also serves their professional (social) needs, and, as it is used, claims to become an element of the lexical system of a general literary language . At the same time, the computer, economic, sports and consumer (including pragmatonyms) global vocabulary of the modern Russian language is most intensively replenished and functioning.